Supporting complex skill learning with digital tools in tertiary education: educator’s perspective - Bernarda Letnar; André Klostermann; Mirko Schmidt (Current Issues in Sport Science)
Introduction Skill acquisition is a multidisciplinary subdiscipline of sport and exercise science (Fransen, et. al. 2021). Understanding the principles underlying the learning of complex sports skills remains limited. This is partly due to challenges of applying rigorous scientific methods to complex real-life tasks outside laboratory environment and limited transferability of findings from simple laboratory-based tasks to real-life complex sports skills learned through years of practice (Yarrow, et. al., 2009). Best practices and experiences of practitioners therefore represent an important contribution in the development of the field. Educators teaching practical lessons in tertiary education play a crucial role in translating research into practice and sharing knowledge with future sports professionals. However, research into their practice approaches remains an underrepresented field. Main aim of this research was therefore to bridge this gap to support evidence-based research by investigating best practices of educators in tertiary education in skill acquisition and their support for students’ autonomous skill learning.